SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-0716
|View full text |Cite
|
Sign up to set email alerts
|

Novel Metrics for Validation of PIV and CFD in IC Engines

Abstract: In-cylinder flow motion has a significant effect on mixture preparation and combustion. Therefore, it is vital that CFD engine simulations are capable of accurately predicting the in-cylinder velocity fields. Highspeed planar Particle Image Velocimetry (PIV) experiments have been performed on a single-cylinder GDI optical engine in order to validate CFD simulations for a range of engine conditions. Novel metrics have been developed to quantify the differences between experimental and simulated velocity fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…A variable timestep is applied during the simulation, and more details about the numerical setup and models used in the study can be found in a previous work. 38 The working fluid in the simulation is chosen as air, which is treated as an ideal gas. Several initial and boundary conditions are adopted directly from the experimental measurements, namely: intake and exhaust valve lifts pressures within the inlet and exhaust runners time-averaged intake, exhaust and main engine coolant temperatures time-averaged intake air volume flow rate…”
Section: Computational Setupmentioning
confidence: 99%
“…A variable timestep is applied during the simulation, and more details about the numerical setup and models used in the study can be found in a previous work. 38 The working fluid in the simulation is chosen as air, which is treated as an ideal gas. Several initial and boundary conditions are adopted directly from the experimental measurements, namely: intake and exhaust valve lifts pressures within the inlet and exhaust runners time-averaged intake, exhaust and main engine coolant temperatures time-averaged intake air volume flow rate…”
Section: Computational Setupmentioning
confidence: 99%
“…The metrics are used to determine a representative mean cycle, to rapidly identify single cycles that provide the best and worst matches to this mean cycle and to quantify the spatial distribution of variability across the tumble plane. For application of these metrics to mean flow fields for validation of CFD simulations using PIV across multiple engine operating points the reader is directed to Scott et al (2019).…”
Section: ) Defined Asmentioning
confidence: 99%
“…The CFD package used linear interpolation between the cell locations to output velocity vectors at the locations of the PIV measurements, due to the minimum cell spacing of 0.7 mm. Comparisons between the tumble ratio predicted by the CFD and the ensemble averaged PIV values have been presented already [23].…”
Section: Numerical Setupmentioning
confidence: 99%
“…For details of the WRI, WMI and CMRI metrics and their application to analysis of flow fields the reader is directed to [22], [23]. A brief summary is provided here for convenience.…”
Section: Quantitative Metrics For Comparison Of Vector Fieldsmentioning
confidence: 99%
See 1 more Smart Citation